Improving Disciplinary Behavior of High School Students through Behavior Contract Technique Counseling - Lailatusa’adah Lailatusa’adah; Nurudducha Nurudducha (International Journal of Counseling and Psychotherapy, 2024)
This study aims to determine the effectiveness of group counseling with behavior contract techniques to reduce undisciplined behavior in the school of students of SMAN 18 Surabaya. This type of classroom action research with qualitative methods is conducted in two cycles. Each cycle consists of four stages, namely planning, implementation, observation, and reflection. The research subjects consisted of four students recorded as tardy seven to thirteen times in one month based on documentation data of tardy records. Data was collected through observation, interviews, and documentation of students' tardiness records at school. In the first cycle, the results of group counseling showed that tardiness was reduced to 2-3 times a week. In the second cycle, there was a significant decrease where there were no undisciplined learners because they already had a strong commitment to comply with the agreed behavior contract. The results of this study indicate that group counseling techniques using behavior contracts are effective in reducing undisciplined behavior in coming to school at SMA Negeri 18 Surabaya.